Mortality following hospital discharge with a diagnosis of eating disorder: national record linkage study, England, 2001-2009. - Hoang, U; Goldacre, M; James, A (2014)
OBJECTIVE: To calculate mortality of people with eating disorders (ED) in England, relative to that of people of the same age and sex, between 2001 and 2009. We were specifically interested in mortality amongst adolescents and young adults (15-24 years), and older adults (25-44 years). METHOD: We analyzed a NHS Hospital Episode Statistics (HES) dataset for all England, linked to death registrations, to calculate age- and sex-specific discharge rates for people with a diagnosis of ED and their subsequent mortality by one year after discharge. RESULTS: The standardized mortality ratio (SMR) for adolescents and young adults with a diagnosis of ED was 7.8 (95% confidence interval: 4.4-11.2). This compares with an SMR for people of the same age with schizophrenia of 10.2 (8.3-12.2), with bipolar disorder of 3.6 (1.1-6.1, and with depression of 4.5 (3.6-5.3). Of the ED, the SMR for anorexia nervosa (AN) in people aged 15-24 was 11.5 (6.0-17.0), for bulimia nervosa (BN) was 4.1 (0-8.7), and eating disorders not otherwise specified (ED NOS) was 1.4 (0-4.0). For older adults aged 25-44 years, the SMR for ED was 10.7 (7.7-13.6). Specifically, for AN was 14.0 (9.2-18.8), for BN was 7.7 (3.5-11.9), and ED NOS was 4.7 (1.4-8.0), for schizophrenia was 7.3 (6.6-7.9), for bipolar disorder was 4.3 (3.5-5.1) and for depression was 4.9 (4.6-5.3). No deaths were recorded below 15 years of age. DISCUSSION: This study confirms the high SMR associated with ED, notably with anorexia and bulimia.